The Pseudomonas Syringae Effector AvrPtoB Associates With and Ubiquitinates Arabidopsis Exocyst Subunit EXO70B1 - Wang, Wei; Liu, Na; Gao, Chenyang; Rui, Lu; Tang, Dingzhong (Frontiers in Plant Science, 2019)
Many bacterial pathogens secret effectors into host cells to disable host defenses and thus promote infection. The exocyst complex functions in the transport and secretion of defense molecules and loss of function of the EXO70B1 subunit leads to autoimmunity by activation of a truncated Toll/interleukin-1 receptor-nucleotide binding sequence protein (TIR-NBS2; herein referred to as TN2). Here, we show that EXO70B1 is required for pathogen-associated molecular pattern-triggered immune responses in Arabidopsis thaliana. The effector AvrPtoB, an E3 ligase from Pseudomonas syringae pv. tomato (Pto) strain DC3000, associates with EXO70B1. AvrPtoB ubiquitinates EXO70B1 and mediates EXO70B1 degradation via the host’s 26S proteasome in a manner requiring E3 ligase activity. AvrPtoB enhances Pto DC3000 virulence by overcoming EXO70B1-mediated resistance. Moreover, overexpression of AvrPtoB in Arabidopsis leads to autoimmunity, which is partially dependent on TN2. Expression of TN2 in tobacco (Nicotiana tabacum and Nicotiana benthamiana) triggers strong and rapid cell death, which is suppressed by co-expression with EXO70B1, but reoccurs when co-expressed with AvrPtoB. Taken together, our data highlight that AvrPtoB targets the Arabidopsis thaliana EXO70 protein family member EXO70B1 to manipulate the defense molecule secretion machinery or immunity.